Optimal Tracheostomy Timing Through Modeling Based on Severity of Vocal Cord Injury. - Malkoc, Aldin; Nguyen, Danny T.; Wong, Stephanie; Wong, David T. (Respiratory Care, 2023)
BACKGROUND: Endotracheal intubation is a routinely performed procedure in the ICU. Whereas it is recognized that endotracheal intubation can result in laryngeal and tracheal injury, this study evaluated factors that may affect the incidence of posterior vocal cord ulcers (PVCUs). METHODS: One thousand three hundred fifty-five patients were retrospectively screened from 2002-2018 that received a tracheostomy with routine bronchoscopy at a single institution. Post tracheostomy operative notes were reviewed and included only if proper visualization of the vocal cords was documented. Primary outcome measures included presence of PVCU, length of time on a ventilator until a tracheostomy, hospital length of stay, and mortality. Stratification of the data focused on the severity of the ulcer (mild, moderate, and severe) and was analyzed using analysis of variance, multivariate analysis, and Kaplan-Meier modeling of PVCU incidence over time. RESULTS: We enrolled 192 subjects with documentation of vocal cord visualization. Thirty-nine subjects did not have a PVCU, whereas 153 subjects did. A median duration of 9 (interquartile range [IQR] 5-13) d was associated with developing a mild PVCU, whereas individuals intubated for a median of 6 (IQR 4-7) d were ulcer free. Statistical difference between length of time on a ventilator before tracheostomy and the severity of the PVCU seen was significant (P < .001). The Kaplan-Meier model showed that beyond 2 weeks of endotracheal intubation subjects will have > 80% chance of developing a moderate vocal cord ulcer. Whereas by day 7, there is only a 20% chance of developing a moderate ulcer. CONCLUSIONS: Earlier tracheostomy placement was associated with reduced severity of vocal cord ulcer formation. The Kaplan-Meier model suggests that waiting for 14 d is likely too long and earlier placement of a tracheostomy, within a week, may decrease the morbidity of posterior vocal cord injury.